Evaluation of Biological Activities and Enzyme Inhibitory Potential of 7,8-Dihydroxy-3-(4-methylphenyl) Coumarin - Sadi, Gokhan; Bora, Hacer; Cicek, Mustafa; Koran, Kenan; Gorgulu, Ahmet Orhan; Yilmaz, Ibrahim (Springernature, 2022)
In this study, antioxidant, antibacterial, cytotoxic, and antioxidant enzyme inhibitory properties of the 7,8-dihydroxy-3-(4-methylphenyl) coumarin were investigated. Its free radical scavenging activity, total antioxidant capacity, and reducing power were as high as standard antioxidants, namely gallic acid and Trolox. It also demonstrated antibacterial effects on tested microorganisms and cytotoxic activity on breast cancer (MCF-7) cells, even though it was non-toxic to hepatocellular carcinoma (HepG2) cells (IC50 for HepG2: 0.553 mM; IC50 for MCF-7: 0.040 mM). 7,8-Dihydroxy-3-(4-methylphenyl) coumarin inhibited catalase enzyme in a dose-dependent manner (IC50 0.12 mM), and the decrease in V-max and K-m values of catalase suggests a mixed-type inhibitory mechanism. Glutathione-S-transferase activities were also suppressed with IC50 3.7 mM for 1-chloro-2,4-dinitrobenzene- and 7.5 mM for glutathione-dependent glutathione-S-transferase activities. While the changes in kinetic parameters indicated a possible competition between 1-chloro-2,4-dinitrobenzene-substrate for glutathione-S-transferase activity, glutathione-dependent glutathione-S-transferase activity is consistent with the mixedtype inhibition model. These results indicated the high antioxidant, antimicrobial, and cytotoxic potential of 7,8-dihydroxy3-(4-methylphenyl) coumarin and inhibitory effects over main antioxidant and detoxification enzymes that might induce oxidative stress and xenobiotic induced apoptosis in cancer cells which would prevent oncogenesis and tumor progression in the liver and breast cancer.
Keywords: Antioxidant power; Catalase; Coumarin Cytotoxicity; Detoxification enzymes; Enzyme inhibition